2021
DOI: 10.1108/jeet-10-2020-0011
|View full text |Cite
|
Sign up to set email alerts
|

Improving awareness of energy conservation: Rocky Mountain City

Abstract: Purpose The purpose of this research project was to improve public awareness to improve public awareness of the importance of energy conservation and to improve the use of simple conservation strategies. A thorough evaluation of the net gain from the numerous energy campaigns rolled out to the public every year is lacking. This study conducted pre- and post-campaign surveys and focus groups to evaluate one campaign’s impact on self-reported energy behaviors. Design/methodology/approach The campaign used tele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(18 reference statements)
1
1
0
Order By: Relevance
“…This can encourage changes in people's behavior and habits when using energy [18]. Similar results were also obtained from research conducted by Esty and Winston, which found that campaigns and outreach related to green entrepreneurship could increase public awareness of saving energy and making good use of natural resources [19].…”
Section: Introductionsupporting
confidence: 70%
“…This can encourage changes in people's behavior and habits when using energy [18]. Similar results were also obtained from research conducted by Esty and Winston, which found that campaigns and outreach related to green entrepreneurship could increase public awareness of saving energy and making good use of natural resources [19].…”
Section: Introductionsupporting
confidence: 70%
“…Public communication campaigns can be defined as purposive attempts to disseminate information or change behaviors in audiences within a specified time using various communication activities and featuring media messages in numerous channels to produce benefits to individuals and society [24]. In addition, most energy conservation communication campaigns are aimed at individual changes in consumer behavior by presenting positive behavior patterns and shaping appropriate habits [13,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%